Anteseden dan Konsekuensi dari Kepuasan Pelanggan: Survei Kepuasan Pelanggan Barbershop di Yogyakarta - Budi Setyanta (Universitas Darussalam Gontor, 2017)
This study aims to identify the influence of perceive quality, price fairness, convenience, and customer satisfaction towards customer loyalty. This research is conducted to provide solution about the phenomenon of rapid growth of barbershop in Yogyakarta. This research is categorized as explanatory research, because it explains the causality relationship between observation variables. The number of samples are 200 respondents according to the requirement of sufficiency of sample in SEM test. Data retrieval is guided by using questionnaires. The results of this study indicate that the perceive quality, price fairness, and convenience have a positive and significant impact towards customer satisfaction, then customer satisfaction has a positive and significant impact towards customer loyalty. This study provides the diversity of previous research because the observed variables and question items are adjusted to the research setting in Indonesia.